Identification of Intermediate- to High-Risk Papillary Thyroid Carcinoma Patients Who May Be Safely Managed without the Performance of Delayed Stimulated Thyroglobulin Measurements following Total Thyroidectomy and Radioactive Iodine Therapy - Kyung-Hee Kim; Min-Hee Kim; Ye-Jee Lim; Ihn Suk Lee; Ja-Seong Bae; Dong-Jun Lim; Ki Hyun Baek; Jong Min Lee; Moo-Il Kang; Bong-Yun Cha (International Journal of Endocrinology, 2015)
Background. The measurement of stimulated thyroglobulin (sTg) after total thyroidectomy and remnant radioactive iodine (RAI) ablation is the gold standard for monitoring disease status in patients with papillary thyroid carcinomas (PTCs). The aim of this study was to determine whether sTg measurement during follow-up can be avoided in intermediate- and high-risk PTC patients. Methods. A total of 346 patients with PTCs with an intermediate or high risk of recurrence were analysed. All of the patients underwent total thyroidectomy as well as remnant RAI ablation and sTg measurements. Preoperative and postoperative parameters were included in the analysis. Results. Among the preoperative parameters, age below 45 years and preoperative Tg above 19.4 ng/mL were significant risk factors for predicting detectable sTg during follow-up. Among the postoperative parameters, thyroid capsular invasion, lymph node metastasis, and ablative Tg above 2.9 ng/mL were independently correlated with a detectable sTg range. The combination of ablative Tg less than 2.9 ng/mL with pre- and postoperative independent risk factors for detectable sTg increased the negative predictive value for detectable sTg up to 98.5%. Conclusions. Based on pre- and postoperative parameters, a substantial proportion of patients with PTCs in the intermediate- and high-risk classes could avoid aggressive follow-up measures.